Pertobatan dan Baptisan dalam Teologi Seteorologi Kisah Para Rasul - Samuel Cibro; Sah Rejeki Sinamo (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This article examines the meaning of repentance and baptism in the Acts of the Apostles through an eschatological theological approach. Repentance and baptism are considered two important aspects in the journey of salvation and the development of the Christian faith. The methodology used in this research is qualitative with a literature study to explore the meaning, application and relationship between repentance and baptism from an eschatological theological perspective. Research findings reveal that repentance is a transformation of the heart that prepares a person to receive baptism as a symbol of new birth and the washing away of sins by the Holy Spirit. These two concepts complement each other and have significant theological consequences in the teaching and practice of the church's faith today. This research provides in-depth insight into the role of repentance and baptism in the context of gradual and eschatological salvation.